2016
DOI: 10.1038/srep34695
|View full text |Cite
|
Sign up to set email alerts
|

A crucial role for spatial distribution in bacterial quorum sensing

Abstract: Quorum sensing (QS) is a process that enables bacteria to communicate using secreted signaling molecules, and then makes a population of bacteria to regulate gene expression collectively and control behavior on a community-wide scale. Theoretical studies of efficiency sensing have suggested that both mass-transfer performance in the local environment and the spatial distribution of cells are key factors affecting QS. Here, an experimental model based on hydrogel microcapsules with a three-dimensional structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 32 publications
5
40
2
Order By: Relevance
“…As microfluidics and laser printing technologies have continued to develop, it has become possible to address these sorts of questions by confining small numbers of bacteria in diffusive picoliter-scale hydrogel traps. One such study in which V. harveyi was trapped showed that aggregates with diameters of about 25 microns demonstrated robust QS while those ≤10 microns showed little QS-dependent gene expression 84 . Similar results were observed for P. aeruginosa, which had been confined in micro-3D printed bacterial ‘lobster traps’.…”
Section: Main Textmentioning
confidence: 99%
“…As microfluidics and laser printing technologies have continued to develop, it has become possible to address these sorts of questions by confining small numbers of bacteria in diffusive picoliter-scale hydrogel traps. One such study in which V. harveyi was trapped showed that aggregates with diameters of about 25 microns demonstrated robust QS while those ≤10 microns showed little QS-dependent gene expression 84 . Similar results were observed for P. aeruginosa, which had been confined in micro-3D printed bacterial ‘lobster traps’.…”
Section: Main Textmentioning
confidence: 99%
“…In biofilms, microorganisms are embedded in a heterogeneous three-dimensional matrix, and the steep chemical or physical gradients that can be found within this matrix imply that isogenic cells often display different phenotypes (Flemming et al 2016;Gao et al 2016). While a few studies provide preliminary insights into this intercellular heterogeneity (eg Tsimring;Carnes et al 2010;Stiegelmeyer and Giddings 2013;Trovato et al 2014;Yu 2014), it is still complex and time-consuming to understand and predict the behaviour of individual cells in a spatially structured consortium.…”
Section: Introductionmentioning
confidence: 99%
“…This analysis revealed clear separations in the distribution of ranked values for each metric of landscape ecology examined (Figure 7a-j), confirming that all were able to discriminate the biofilm architectures of these two communities developed on contrasting substrata. Consistent with the visual evidence provided by representative biofilm images (Figure 1a-f), these data further corroborate that the microcolony biofilms of community B developed a more dense and discrete landscape pattern, interpreted as having more productivity (more aggregated patches and larger sizes covering a significantly larger portion of the substratum area, hence less void spaces), greater edge intensities and complex shapes enabling their greater exploitation of external resources, significantly enhanced connectivity between neighboring microcolony patches (often via thin filamentous interconnections; see Figure 1b,f) that would potentially extend their "calling distances" in cell-cell communication, and more access to additional opportunities for syntrophic-like cross-feeding and other positive interactions with community members, ultimately resulting in further growth expansion on the polystyrene substratum [5,18,24,29,38,[53][54][55][56]61,62]. These architectural differences between the two communities of microcolony biofilms prompted us to explore the fractal geometry component of their landscape architecture.…”
Section: Landscape Ecology Of River Microbial Biofilms At Microcolonymentioning
confidence: 99%